Analisis Pengendalian Kualitas Produk Part Housing SUV Menggunakan Metode Statistical Process Control di PT. Y - Fadhilah, Nurul Amalia; Arifin, Jauhari (Fakultas Teknik Universitas Tulang Bawang, 2024)
In the increasingly advanced world of manufacturing industries, of course, companies need to innovate for tighter competition. The role of product quality will be very influential to get product results with good quality and in accordance with standard operating procedures, must carry out quality control by paying attention to the level of product defects in order to approach zero defects. Therefore, this study aims to analyze quality control to reduce the occurrence of defective products and provide improvement proposals. The method used is Statistical Process Control (SPC) to analyze product defects with the total production of SUV Housing Parts as many as 34740 units. 4 types of defects were produced, namely Coak Blank 40 units, Overlap 37 units, Ngecap Scrap 13 units, and Flatness NG 11 units. The factors causing this type of disability are human factors, machines, materials, environment, and methods. Thus, the improvement proposals given are providing regular training to operators, carrying out routine machine maintenance, using ear plugs while working, measuring material dimensions, and checking materials that will enter the machine. Based on the research conducted, this SPC method can help companies identify product defects and provide suggestions or solutions to problems that occur. Keywords: Defect, Quality Control, Repair, Statistical Process Control